Expression of Beta-Defensin 131 Promotes an Innate Immune Response in Human Prostate Epithelial Cells - Kim, Jung Hoon; Kim, Kyeoung-Hwa; Kim, Hae Jong; Lee, Jaehyouk; Myung, Soon Chul (PLOS ONE, 2015)
Previously, using the Illumina HumanHT-12 microarray we found that β-defensin 131 (DEFB131), an antimicrobial peptide, is upregulated in the human prostate epithelial cell line RWPE-1 upon stimulation with lipoteichoic acid (LTA; a gram-positive bacterial component), than that in the untreated RWPE-1 cells. In the current study, we aimed to investigate the role of DEFB131 in RWPE-1 cells during bacterial infection. We examined the intracellular signaling pathways and nuclear responses in RWPE-1 cells that contribute to DEFB131 gene induction upon stimulation with LTA. Chromatin immunoprecipitation was performed to determine whether NF-κB directly binds to the DEFB131 promoter after LTA stimulation in RWPE-1 cells. We found that DEFB131 expression was induced by LTA stimulation through TLR2 and p38MAPK/NF-κB activation, which was evident in the phosphorylation of both p38MAPK and IκBα. We also found that SB203580 and Bay11-7082, inhibitors of p38MAPK and NF-κB, respectively, suppressed LTA-induced DEFB131 expression. The chromatin immunoprecipitation assay showed that NF-κB directly binds to the DEFB131 promoter, suggesting that NF-κB is a direct regulator, and is necessary for LTA-induced DEFB131 expression in RWPE-1 cells. Interestingly, with DEFB131 overexpression in RWPE-1 cells, the accumulation of mRNA and protein secretion of cytokines (IL-1α, IL-1β, IL-6, and IL-12α) and chemokines (CCL20, CCL22, and CXCL8) were significantly enhanced. In addition, DEFB131-transfected RWPE-1 cells markedly induced chemotactic activity in THP-1 monocytes. We concluded that DEFB131 induces cytokine and chemokine upregulation through the TLR2/NF-κB signaling pathway in RWPE-1 cells during bacterial infection and promotes an innate immune response.